DcR3 promotes proliferation and invasion of pancreatic cancer via a DcR3/STAT1/IRF1 feedback loop - Wei, Yijun (Am J Cancer Res, 2019)
Pancreatic cancer (PC) is one of the most common gastrointestinal malignancies that are highly aggressive with a low 5-year survival rate. Accumulated evidence has indicated that decoy receptor 3 (DcR3) is involved in several pathologic processes and various cancers. However, the mechanisms underlying dysregulated DcR3 expression and activation in PC remain to be fully established. In this study, we investigate the function and regulatory network of DcR3 in PC. We found that DcR3 was upregulated in PC tissues and serum. High DcR3 expression was associated with aggressive clinicopathological features and poor prognosis. Functionally, DcR3 not only increased cell migration and invasion in vitro but also promoted tumour growth both in vitro and in vivo by loss-of-function and gain-of-function experiments. Mechanistically, DcR3 promoted the phosphorylation of signal transducers and activators of transcription 1 (STAT1), leading to a dramatic increase in interferon regulatory factor 1 (IRF1). IRF1 then increased the transcriptional activity of DcR3, forming a positive feedback loop to reinforce DcR3 expression. In addition, DcR3 promoted carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) expression through activated IRF1. In conclusion, our findings provided novel insights into the function and mechanism of DcR3 in the pathogenesis of PC, which may be a potential therapeutic target for PC.